Diseño de un modelo logístico para el servicio postventa en los CST para el sector automotriz (2018)
The logistics of the after-sales service oriented towards intangible and intangible products, is crucial for the organizations that nowadays are aiming at attracting clients. It is necessary that these organizations are hand in hand with information and communication technologies, the use of the internet and other tools that allow you to attend each of the truth moments that are created in the after-sales service, that is, always that the client has the ability to evaluate the service offered by the company, this will be exposed to an evaluation by the client where finally it will decide whether or not to return to the company. Becoming a dynamic model that meets each request, complaints and claims with a management that comes from the internal customers located in the focal company of a value network.